A Case of Asymptomatic Postmenopausal Hematometra Mimicking Endometrial Carcinoma - Güven, Süleyman; Ilıca, Turan; Yılmaz, Alpay; Alanbay, İbrahim (Gynecology Obstetrics & Reproductive Medicine, 2007)
Hematometra in a postmenopausal woman is a rare condition and the possible association of endometrial and cervical carcinoma should be excluded for such cases. We report the case of a 66-year-old multiparous postmenopausal woman who presented as an asymptomatical hematometra mimicking endometrial carcinoma. In this case, hematometra was demonstrated by sonography and well defined by computed tomography and MRI and suggested the possible diagnosis of endometrial cancer. Endometrial sampling revealed only the diagnosis of blood clots and scanty endometrial strands. A total hysterectomy with bilateral salpingo-oophorectomy were done. Pathologic evaluation excluded the diagnosis of endometrial carcinoma and revealed senile cervical stenosis possibly due to hypoestrogenic state. The successful management of this rare condition was discussed.